Análise Transcriptômica de Genes com Função Putativa na Diferenciação Sexual de Physcomitrium patens - Ferreira , Tiego de La Vega (2023)
Understanding sexual differentiation in mosses, such as P. patens, has significantly advanced with the identification of a network of putative genes involved in this process. This network includes genes that regulate the development of reproductive organs and cell signaling during sexual differentiation. The methodology involved the analysis of transcripts from specific gametogenic tissues and comparison with genes expressed in male and female gametophytic tissues. This allowed the identification of differentially expressed genes involved in sexual differentiation, contributing to a deeper understanding of the molecular mechanisms underlying the evolution of sexual development in non-vascular mosses. Quantitative analysis of the transcripts revealed the expression of over thirty-two thousand genes, with approximately 36% showing null or low expression in both gametophytic tissues, indicating that a significant portion of the genome is not directly related to sexual differentiation. However, approximately 6.8% and 6.5% of genes showed null or low expression exclusively in the antheridia or archegonia, respectively. Additionally, about 35% of genes were expressed in both tissues, suggesting a possible contribution to the sexual maturation of the organism. The results also highlighted genes that were exclusively overexpressed in antheridia or archegonia, as well as genes underexpressed in one tissue and overexpressed in the other. These genes are associated with functions such as gene regulation, membrane formation, sperm-egg interaction, and cell transport, demonstrating the complex genetic regulation involved in the sexual differentiation of P. patens. Furthermore, the analysis revealed that sexual differentiation in mosses may be influenced by genetic factors including the presence of sex chromosomes and polyploidy. In summary, the research provides important insights into the mechanisms of sexual differentiation in mosses, contributing not only to understanding the evolution of sexual development but also to advancing knowledge in plant biology.